PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE INKUIRI DI KELAS V SD NEGERI - KHAIRIL, KHAIRIL (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This method gives students the chance to think, train students memrcahkan msalah find their own answers. Research objectives were to describe the increase in science learning outcomes using the inquiry. The research was conducted in the first semester of the school year 2012/2013 in SD N 06 Situjuah Batua County District Situjuah Limo Nagari Fifty Cities. The study was Classroom Action Research (CAR) with qualitative and quantitative approaches. This study conducted two cycles, cycle 1 held 2 meetingsandcycleIIheld1meeting. The results of the research cycle 1 1 meeting in RPP got enough percentage of 71.4%, cycle 1 meeting 2 92.8% , on the second cycle 1 meeting 96.4% . The average yield was 82.1% first cycle. In the second cycle 96.4% , then the average - average cycle I and cycle II was 89.25% . Assessment of aspects of teachers in cycle 1 pertmuan 1 for 79.7% cycle 1 meeting 2 the average percentage of 83.6% Well, the first meeting of the second cycle of 96.9% Very Good average cycle 1 and cycle II to obtain the percentage of 90.25% Very Good. From the aspect of cycle 1 meeting 1 for 71.4%, cycle 1 meeting 2 by 82% Both the average percentage of 76.5% first cycle, second cycle 1 meeting by 89% Good Once, the average cycle 1 and cycle II of 82.75%. From the results of student learning cycle 1 meeting 1 for 62 Enough, at cycle 1 meeting 2 average 80 Well, on the second cycle of 86 .   Kata Kunci : peningkatan;hasil belajar IPA; metode; inkuiri